Cyclosporine-a and bone density around titanium implants: a histometric study in rabbits - Celso Eduardo Sakakura; Beatriz Maria Valério Lopes; Rogério Margonar; Thallita Pereira Queiroz; Francisco Humberto Nociti Júnior; Elcio Marcantonio Júnior (Ariesdue, 2011)
Aim: Cyclosporine A (CsA) is an immunosuppressive agent commonly used to prevent organ transplantation rejection. It has been demonstrated that CsA may negatively affect osseointegration around dental implants. Therefore, the aim of this study was to evaluate the effect of CsA administration on bone density around titanium dental implants. Materials and Methods: Fourteen New Zealand rabbits were randomly divided into 2 groups with seven animals each. The test group (CsA) received daily subcutaneous injection of CsA (10mg/kg body weight) and the control group (CTL) received saline solution by the same route of administration. Three days after the beginning of immunosuppressive therapy, one machined dental implant (7.00 mm in lenght and 3.75 mm in diameter) was inserted bilaterally at the region of the tibial methaphysis. After 4 and 8 weeks the animals were sacrificed and the histometrical procedures were performed to analyse the bone density around the first four threads of the coronal part of the implant. Results: A significant increase in the bone density was observed from the 4- to the 8 week-period in the control group (37.41% + 14.85 versus 58.23% + 16.38 - p < 0.01). In contrast, bone density consistently decreased in the test group overtime (46.31% + 17.38 versus 16.28 + 5.08 - p <0.05). In the 8-week period, there was a significant difference in bone density between the control and the test groups (58.23 + 16.38 eand16.28 + 5.08 - p= 0.001). Conclusion: Within the limits of this study, long-term CsA administration may reduce bone density around titanium dental implants during the osseointegration process.